Preoperative Evaluation of the Curative Resectability of Gastric Cancer by Abdominal Computed Tomography and Ultrasonography: A Prospective Comparison Study - Kim, Jae-Jun (Korean J Intern Med, 1997)
OBJECTIVES: We compared the ability of preoperative abdominal computed tomography (CT) with that of preoperative abdominal ultrasonography (US) in predicting the extent of tumor growth and the curative resectability of gastric cancer. METHODS: Abdominal CT and US were done in 95 patients with gastric adenocarcinoma. The radiologic findings were prospectively compared with surgical and pathologic findings. RESULTS: The sensitivities of abdominal CT and US in detecting the perigastric lymph node involvement were 26.6% and 20%, respectively. The sensitivity of abdominal CT in predicting the pancreatic invasion (60%) was better than that of abdominal US (20%). However, there were 6 false positive diagnosis of pancreatic invasion by abdominal CT; in contrast, there was no false positive diagnosis of pancreatic invasion by abdominal US. Of 95 patients who underwent surgical exploration, 14 were found to have unresectable tumors because of extragastric organ involvement and distant metastases. Abdominal CT falsely predicted 8 of 74 cases in which curative gastric resection was impossible as resectable. Moreover, abdominal CT falsely predicted 5 of 81 cases in which curative gastric resection was possible as unresectable. Abdominal US falsely predicted 12 of 14 cases in which curative surgery was impossible as resectable. CONCLUSION: Preoperative abdominal CT and US did not accurately predict the tumor extent and the curative resectability of the gastric cancer. Especially, abdominal CT finding of pancreatic invasion by gastric cancer should not be a contraindication for surgical exploration.